Analysis Of Nabr Wa Tanghim Errors In Arabic Conversations Among Students - Hijriyah, Athiyah Laila; Musthofa, Tulus; Nasiruddin, Nasiruddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research focuses on studying Arabic language errors in conversation, specifically nabr wa tanghim, in phonological studies. This study aims to describe language errors, classify them, analyze their form, evaluate errors, and examine the primary factors that contribute to these errors. The subjects in this research were students of the PBA Masters Program at UIN Sunan Kalijaga Yogyakarta, Indonesia. The approach used in this study is descriptive-qualitative, with data collection techniques using observation, interviews, and documentation. The data analysis used is a structured approach that includes data collection, identification, error analysis, error classification, determining error patterns, and offering evaluation. The results of the investigation revealed that language errors commonly made by students during oral communication, especially in the theme ofندوة عن العولمة, were still relatively high. Many errors occur in interrogative sentences and statements. Thisis caused by students' lack of understanding regarding the rules of nabr wa tanghim. Students pay more attention to duration, fluency, and morphological aspects in conversation and are confident if they can babble. Two categories of factors cause language errors: internal factors, which originate from within the speaker, and external factors, which arise from the influence of the environment around the speaker. The alternative to this problem is to understand more deeply the rules of nabr wa tanghim, often listen to pronunciations from native speakers, practice and evaluate independently, and utilize learning media.